Human activity in covered urban space a case study of Petaling street, Kuala Lumpur, Malaysia - Sulaiman, Ahmad Bashri; Abu Baker Omar, A Karit. Alla; M. Senan, Lutfi Ali (2008)

(untitled)
Streets are channels of movement and a symbolic representation of local tradition and culture. In South East Asian cities like Kuala Lumpur, Malaysia, they are avenues for socialization just as what plazas are in Europe. They are publicly acknowledged joints for entertainment of peer groups, family members, and guests alike. The physical quality of a street determines the human activities it could support. The changing identity of Petaling Street activity character with the introduction of a permanent cover for the traditional market altered its original activity pattern. It is therefore imperative to evaluate the impact of the new physical environment on human activities within it. The behavioural analysis of the covered street was conducted to appraise its ability to support or restrict human behaviour. User activities of the environment were observed systematically to establish behaviour pattern of the street. Behavioural mapping, behaviour categorisation and behaviour analysis were carried out to identify the functional characteristics associated with covered streets. The research findings show that there is a very strong functional characteristic of the covered street which is consistent with theories of environmental quality enhances human activity. They play a very important role in determining the user of the street, their activities and behavioural patterns. It also realized that the built environment could be to be manipulated to control human behaviour. The research identified that elements such as pedestrian comfort and adjacent land uses appear to influence the level of use within the pedestrian malls. This research will enhance the understanding of design decisions at different scales, such as the introduction of covered streets in Malaysian traditional markets like Petaling Street.